Organizational Hierarchy: A Critique of Power and Interdependence - Estre, Felipe Bernardo (Faculdade de Filosofia e Ciências, 2019)
The article intends to rethink the inequality in International Relations based on the book Power and interdependence, published in 1977 by Robert Keohane and Joseph Nye. Relying on discourse analysis, it is argued that, contrary to what the authors say, the new political processes that characterize international politics since the beginning of the twentieth century did not resulted necessarily in the decrease of international hierarchy. On the contrary, international organizations allow the articulation of other forms of discrimination among the states that cannot be reduced to economic factors or asymmetries of power. The core discussion about inequality in the work of Keohane and Nye is on the very concept of complex interdependence, which divides the international system between the "advanced" or "pluralistic, industrialized," and those that cannot join this group without the proper adjustments. Therefore, international organizations would not be factors that decrease the hierarchy in the international system but are reproducing inequality through the allocation of “organizationally dependent capabilities”.